Development and characterization of PLA and Cassava starch‐based novel biodegradable film used for food packaging application. Issue 9 (12th January 2022) - Mangaraj, Shukadev; Thakur, Rajeev Ranjan; Yadav, Ajay
Abstract: Pure starch like PLA is an outstanding substitute to prepare packaging film, nevertheless, because of its greater hydrophilicity, mixing it with other starch become essential. Cassava is a root vegetable that is an excellent source of starch, and it can be used to prepare bio‐based packaging materials. The packaging films were developed by blown film extrusion method using 10% and 20% cassava starch, blended with PLA. The water vapor barrier property, and other physico‐chemical properties of the packaging films were determined, and it was observed that the film characteristics of PLA and Cassava starch up to 20%, were equally suitable for packaging application to virgin PLA‐based film. The biodegradable film developed for MA packaging, had a potential to retain the quality attributes of capsicum up to 12 and 24 days at 25°C and 8°C, respectively as compared to the shelf‐life of unpackaged capsicum viz. 4 and 9 days at respective temperatures. Novelty impact statement: The film characteristics like haze %, tensile strength, OTR and WVTR parameters for PLA, and 20% cassava starch were found to be 89.68%, 25.16 MPa, 123.92 cc/m 2 /day, and 217 gm/m 2 /day, respectively. The physico‐chemical characteristics of the developed packaging films were found to be better as compared to other starch and PLA blended film. The outcomes of biodegradable film‐based MA packaging were compared to a non‐biodegradable film‐based MA packaging of capsicum, it was observed that the application of biodegradable film offers a new alternative over the non‐biodegradable polymeric film for MA packaging of fresh produce without compromising its quality.